Career Growth, Lean Leadership, and Turnover Intention: The Mediating Role of Employee Engagement Among Generation Z in the FMCG Industry - Yoan Nita Estera; Yenny Maya Dora (Dinasti Publisher, 2026)
High turnover among Generation Z employees has become a critical challenge for the fast-moving consumer goods (FMCG) industry, disrupting operational continuity and increasing organizational costs. Although career growth and leadership are recognized determinants of turnover intention, limited evidence explains how career growth and human-centered lean leadership reduce turnover intention through employee engagement among Generation Z employees in the FMCG industry. Grounded primarily in Social Exchange Theory and the Job Demands–Resources framework, this study develops and tests an engagement-based retention model. Data from 344 Generation Z production employees at an FMCG company in West Java, Indonesia, were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results show that career growth and lean leadership significantly enhance employee engagement and reduce turnover intention, with engagement serving as the principal mechanism linking both resources to retention; for lean leadership, the indirect effect exceeds the direct effect. The proposed model demonstrates strong explanatory power for both employee engagement and turnover intention. Importance–Performance Map Analysis (IPMA) identifies career growth, particularly promotion speed and remuneration growth, as the highest priority for improvement. Theoretically, this study contributes to the retention literature by integrating career growth, human-centered lean leadership, and employee engagement into a comprehensive retention model, while offering actionable insights for transparent career systems and human-centered leadership practices.